Pengaruh Konsumsi Energi dan Kemajuan Teknologi terhadap Pertumbuhan Ekonomi Indonesia - Fevriera, Sotya; Hartatdji, Sheilla (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Economic growth describes how economic activities in a country generates additional income for the society in that country in a certain period. Research on the impact of energy and technological progress on Indonesia’s economic growth is relatively limited. The aim of this research is to analyze the impact of energy consumption and technology advance (energy intensity), along with employment (+15) to population ratio and gross capital formulation on Indonesia’s economic growth. Data used in this research is time series data for period 1990-2021 dan analytic technique employed is multiple regression model estimated using ordinary least square (OLS) approach. This research finds that energy consumption has a positive effect and technology advance has a positive effect (energy intensity has a negative effect) on the economic growth. This research also finds that gross capital formulation and employment (+15) to population ratio has no effect on the economic growth.